Beginning XML with C# 2008 From Novice to Professional - Joshi, Bipin. (Apress : Imprint: Apress, 2008)
Beginning XML with C# 2008 focuses on XML and how it is used within .NET 3.5. As you'd expect of a modern application framework, .NET 3.5 has extensive support for XML in everything from data access to configuration, from raw parsing to code documentation. This book demystifies all of this. It explains the basics of XML as well as the namespaces and objects you need to know in order to work efficiently with XML. You will see clear, practical examples that illustrate best practices in action. With this book, you'll learn everything you need to know from the basics of reading and writing XML data to using the DOM, from LINQ and SQL Server integration to SOAP and web services.